Glycoproteomics using fluid‐based specimens in the discovery of lung cancer protein biomarkers: Promise and challenge. Issue 1 (22nd January 2013) - Li, Qing Kay; Gabrielson, Ed; Askin, Frederic; Chan, Daniel W.; Zhang, Hui; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> Lung cancer is the leading cancer in the United States and worldwide. In spite of the rapid progression in personalized treatments, the overall survival rate of lung cancer patients is still suboptimal. Over the past decade, tremendous efforts have been focused on the discovery of protein biomarkers to facilitate the early detection and monitoring of lung cancer progression during treatment. In addition to tumor tissues and cancer cell lines, a variety of biological material has been studied. Particularly in recent years, studies using fluid‐based specimen or so‐called "fluid‐biopsy" specimens have progressed rapidly. Fluid specimens are relatively easier to collect than tumor tissue, and they can be repeatedly sampled during the disease progression. Glycoproteins are the major content of fluid specimens and have long been recognized to play fundamental roles in many physiological and pathological processes. In this review, we focus the discussion on recent advances of glycoproteomics, particularly in the identification of potential glyco protein biomarkers using fluid‐based specimens in lung cancer. The purpose of this review is to summarize current strategies, achievements, and perspectives in the field. This insight will highlight the discovery of tumor‐associated glycoprotein biomarkers in lung cancer and their potential clinical applications.